Floristic Survey of Riparian Forest in Areas of Clay Extraction in the City of São Roque do Canaã-Es - Gerson Freitas Junior; Zildo Gallo; Flávia Cristina Sossae; Marcus C. Avezum Alves de Castro (Revista Brasileira Multidisciplinar - ReBraM /Brazilian Multidisciplinay Journal, 2015)
The city of São Roque do Canaã (ES) stands out in the production of ceramic objects, but this activity has caused negative environmental impacts in the riparian forest of Santa Maria do Rio Doce river. So, this research had as aim to study the floristic composition of the riparian forest in areas of clay extraction in the city of São Roque do Canaã (ES) to help in the revegetation with native species. The studied area has changed a lot because of mining activities, which can be demonstrated by the shortage of the number of species found in the floristic survey. In spite of observing the presence of several species, pioneer and e initial secondary species, it was observed that the mineral exploration has caused the loss of the superficial layer of the soil, rich in organic material, leading to a reduction of the ecosystem productive capacity.